2006
DOI: 10.1021/bi060935d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Affinity for Aminoglycoside Binding to the Aminoglycoside Nucleotidyltransferase(2‘ ‘)-Ia

Abstract: One of the most commonly occurring aminoglycoside resistance enzymes is aminoglycoside 2''-O-nucleotidyltransferase [ANT(2'')]. In the present study molecular determinants of affinity and specificity for aminoglycoside binding to this enzyme are investigated using isothermal titration calorimetry (ITC). Binding of aminoglycosides is enthalpically driven accompanied by negative entropy changes. The presence of metal-nucleotide increases the affinity for all but one of the aminoglycosides studied but has no effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
(51 reference statements)
1
6
1
Order By: Relevance
“…The net deprotonation, Δ n, was −0.22 ± 0.1 and −0.32 ± 0.1 for the binary and ternary complexes, respectively. This is quite different than what was observed with highly promiscuous aminoglycoside modifying enzymes where all titrations yielded positive slopes in such plots indicating an overall net proton uptake …”
Section: Resultscontrasting
confidence: 91%
See 2 more Smart Citations
“…The net deprotonation, Δ n, was −0.22 ± 0.1 and −0.32 ± 0.1 for the binary and ternary complexes, respectively. This is quite different than what was observed with highly promiscuous aminoglycoside modifying enzymes where all titrations yielded positive slopes in such plots indicating an overall net proton uptake …”
Section: Resultscontrasting
confidence: 91%
“…The last thermodynamic parameter, the change in heat capacity (ΔCp), was determined from the temperature dependence of the binding enthalpy. Solvent reorganization is one of the main contributors to ΔCp, and earlier observations with several, highly promiscuous, aminoglycoside modifying enzymes showed that solvent reorganization played an important role in the formation of enzyme–aminoglycoside complexes . Therefore, to determine effects of solvent, binding experiments were performed in H 2 O and D 2 O.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By isothermal titration calorimetry (ITC), we determined the thermodynamic parameters, and consequently the binding affinities, of aminoglycoside binding to APH(2″)-IVa. Although ITC has been used extensively to characterize aminoglycoside binding to APH(3′)-IIIa [29] , [30] , [31] , [32] or to other aminoglycoside modifying enzymes [33] , [34] , [35] , [36] , [37] , [38] , [39] , this work brings the first data for APH(2″)-IVa. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to what is observed with the aminoglycoside nucleotidyltransferase(2″)-Ia, to which neomycins bind tighter but are not substrates of the enzyme. In this case, the 2″-site becomes too distant to the α-phosphate group for a direct nucleophilic attack [35] . Thus, unfavorable orientation of the 2″-site in the more constrained binding site on APH(2″)-IVa may be correlated with its inability to catalyze phosphotransfer with 4,5-disubstituted aminoglycosides.…”
Section: Discussionmentioning
confidence: 99%